Pengembangan Sistem Aplikasi E-Kaizen Berbasis Website Menggunakan Metode Agile (Studi Kasus PT Cataler Indonesia) - Maulana, Donny; Surojudin, Nurhadi; Juluw, Sephia Maharani Niki (Journal of Practical Computer Science, 2024)
Technological developments are increasingly developing with technological developments, the activities carried out benefit many parties, one of which is in the manufacturing industry. PT Cataler Indonesia is still experiencing difficulties in the keizen application process because it still uses manual, namely using Microsoft Excel, data collection is in the form of paper, this is prone to data loss or document damage. Therefore, it is necessary to carry out research to develop a website-based e-kaizen application system. The aim of this research is to make it easier for employees to submit kaizen applications and process kaizen data. The method used is the Agile Method, a software development that emphasizes flexibility and responsiveness to change. In implementing the e-kaizen system, it uses the Javascript programming language and Firebase as the database. Based on the research, it can be concluded that the development of a website-based e-kaizen application system that replaces manual processes really supports the fulfillment of needs quickly, accurately and with more updates.